2008
DOI: 10.1038/ismej.2008.83
|View full text |Cite
|
Sign up to set email alerts
|

Transport functions dominate the SAR11 metaproteome at low-nutrient extremes in the Sargasso Sea

Abstract: The northwestern Sargasso Sea undergoes annual cycles of productivity with increased production in spring corresponding to periods of upwelling, and oligotrophy in summer and autumn, when the water column becomes highly stratified. The biological productivity of this region is reduced during stratified periods as a result of low concentrations of phosphorus and nitrogen in the euphotic zone. To better understand the mechanisms of microbial survival in this oligotrophic environment, we used capillary liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
320
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(360 citation statements)
references
References 67 publications
32
320
0
Order By: Relevance
“…Consistent with this, there is a transcript encoding an alkaline phosphatase enzyme, which hydrolyzes phosphate from dissolved organic phosphorus, and there are several transcripts encoding exopolyphosphatases (ppX), an enzyme involved in the breakdown of polyphosphate stores. A recent proteome study in the lowphosphorus Sargasso Sea identified phosphate binding and transport, a dominant feature of the SAR11, Prochlorococcus and Synechococcus metaproteome (Sowell et al, 2009). In this study, there are similarly a number of transcripts associated with the high-affinity uptake of phosphate, including pstsS/sphX and a possible pstB transcript in Crocosphaera.…”
Section: Transcript Library Gene Orthologsmentioning
confidence: 68%
“…Consistent with this, there is a transcript encoding an alkaline phosphatase enzyme, which hydrolyzes phosphate from dissolved organic phosphorus, and there are several transcripts encoding exopolyphosphatases (ppX), an enzyme involved in the breakdown of polyphosphate stores. A recent proteome study in the lowphosphorus Sargasso Sea identified phosphate binding and transport, a dominant feature of the SAR11, Prochlorococcus and Synechococcus metaproteome (Sowell et al, 2009). In this study, there are similarly a number of transcripts associated with the high-affinity uptake of phosphate, including pstsS/sphX and a possible pstB transcript in Crocosphaera.…”
Section: Transcript Library Gene Orthologsmentioning
confidence: 68%
“…So far the genomic and physiological properties that distinguish the ecotypes of SAR11 have not been reported; most of what is known was determined from the study of coastal isolates from subclade Ia (Giovannoni et al, 2005a;Tripp et al, 2008a, b) and metagenomic and metaproteomic data (Venter et al, 2004;Wilhelm et al, 2007;Sowell et al, 2008). These organisms have the smallest genomes known for free-living heterotrophic cells, an apparent consequence of genome streamlining and reduction driven by the selection for efficient growth in oligotrophic ocean habitats (Giovannoni et al, 2005a).…”
Section: Geochemical Patterns At Bats and Sar11 Metabolismmentioning
confidence: 99%
“…We compared our predictions of gene expression with two available metaproteomic studies that provided abundances of a comparably large number of proteins, the Sargasso Sea metaproteomic study (17) and a functionally (COG) classified subset of the human gut metaproteomic study (18). The predicted expression values based on CU optimization positively correlate with abundance in metaproteomic studies ( …”
Section: Validation With Metaproteomics Datamentioning
confidence: 99%
“…Even though there is an abundance of available metagenomic data, analogous studies of the whole proteome complement of an environment (17)(18)(19) are in their infancy and their throughput cannot rival that of metagenomics. Therefore, the most accessible approach to define communities at the level of proteome content will in the near future remain (meta)genome-based.…”
Section: In-silico Metaproteomicsmentioning
confidence: 99%
See 1 more Smart Citation